2020
DOI: 10.21608/asnj.2020.80494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Nursing Protocol on Minimizing Venous Thromboembolism for Patients Undergoing Simultaneously Arthroscopic ACLR and High Tibial Osteotomy

Abstract: Background: Venous thromboembolism (VTE) refers to a blood clot that starts in a vein. It includes both deep vein thrombosis and pulmonary embolism. Aim: Evaluate the effect of implementation of educational nursing protocol on minimizing VTE for patients undergoing simultaneously arthroscopic anterior cruciate ligament reconstruction (ACLR) and high tibial osteotomy (HTO). Research design: Quasi experimental (Pre/posttest) research design was utilized. Subjects: A convenient sample of 30 adult patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…As regard to drinking caffeine, it was observed that more than half of the patients in control and study groups were drinking caffeine. This agree with Garrett et al,(2021) (35) , who reported Vol. 28.…”
Section: Discussionsupporting
confidence: 93%
“…As regard to drinking caffeine, it was observed that more than half of the patients in control and study groups were drinking caffeine. This agree with Garrett et al,(2021) (35) , who reported Vol. 28.…”
Section: Discussionsupporting
confidence: 93%